2015
DOI: 10.1089/ast.2015.1309
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Adsorption of Nucleic Acid Bases onto Ferrihydrite via Fourier Transform Infrared and Surface-Enhanced Raman Spectroscopy and X-ray Diffractometry

Abstract: Minerals could have played an important role in concentration, protection, and polymerization of biomolecules. Although iron is the fourth most abundant element in Earth's crust, there are few works in the literature that describe the use of iron oxide-hydroxide in prebiotic chemistry experiments. In the present work, the interaction of adenine, thymine, and uracil with ferrihydrite was studied under conditions that resemble those of prebiotic Earth. At acidic pH, anions in artificial seawater decreased the pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
0
12
0
4
Order By: Relevance
“…Of course, control experiments (in distilled water) are necessary to provide an idea of the effect of the ions. We observed that this seawater influences the stability of minerals and the adsorption of nucleic acid bases (Anizelli et al ., 2015, 2016; Canhisares-Filho et al ., 2015; Carneiro et al ., 2017; Villafañe-Barajas et al ., 2018; Zaia et al ., 2018). In addition, the interaction of cations of seawater (Ca 2+ , Mg 2+ , Sr 2+ and Na + ) with nucleic acid bases changed their reactivity (Anizelli et al ., 2014; Baú et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, control experiments (in distilled water) are necessary to provide an idea of the effect of the ions. We observed that this seawater influences the stability of minerals and the adsorption of nucleic acid bases (Anizelli et al ., 2015, 2016; Canhisares-Filho et al ., 2015; Carneiro et al ., 2017; Villafañe-Barajas et al ., 2018; Zaia et al ., 2018). In addition, the interaction of cations of seawater (Ca 2+ , Mg 2+ , Sr 2+ and Na + ) with nucleic acid bases changed their reactivity (Anizelli et al ., 2014; Baú et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the work of Izawa et al (2010), who performed an experiment through leaching of meteorite samples in Tagish Lake, Zaia (2012) suggested a model of artificial seawater. For several years our group has been working with this artificial seawater model, which probably better resembles the major ions of the ocean of the prebiotic Earth (Anizelli et al, 2014(Anizelli et al, , 2015(Anizelli et al, , 2016Canhisares-Filho et al, 2015;Carneiro et al, 2017;Villafañe-Barajas et al, 2018;Zaia et al, 2018;Baú et al, 2019). Unlike the seawater in the oceans today that have a high concentration of Na + and Cl − (Bearman, 2004), this artificial seawater contains high concentrations of Mg 2+ and SO 4 2− (Zaia, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in such environments, ferrihydrite could be synthesized and maybe an intermediary for the synthesis of hematite, goethite and lepidocrocite (Rzepa et al, 2016;Bassez, 2018). In addition to a number of applications in science and technology (Cornell and Schwertmann, 2003), several iron oxides have been used in prebiotic chemistry experiments such as sorption of biomolecules or precursors of biomolecules (Matrajt and Blanot, 2004;Vieira et al, 2011;Shanker et al, 2013;Canhisares-Filho et al, 2015;Farias et al, 2016;Zaia et al, 2020), catalyzation of the formation of biomolecules (Shanker et al, 2011;Bizzarri et al, 2018;Barge et al, 2019) and catalysation of the formation of biopolymers (Matrajt and Blanot, 2004;Shanker et al, 2012;Georgelin et al, 2017).…”
Section: A-feooh + 3h +mentioning
confidence: 99%
“…The longevity of mineral adsorbed DNA depends on a range of factors where in particular mineral species ( Lorenz and Wackernagel, 1987 ; Cao et al, 2011 ; Michalkova et al, 2011 ; Feuillie et al, 2013 ; Canhisares-Filho et al, 2015 ; Pedreira-Segade et al, 2016 ), background ions ( Lorenz and Wackernagel, 1987 ; Nguyen and Chen, 2007 ; Lu et al, 2010 ), salinity, and pH ( Greaves and Wilson, 1969 ; Saeki et al, 2010 ; Michalkova et al, 2011 ; Feuillie et al, 2015 ; Maity et al, 2015 ) determine the DNA adsorption capacity of a mineral. Depending on the crystalline structure and composition, the surface charge of most minerals changes as a function of pH.…”
Section: Factors Influencing Mineral Facilitated Hgtmentioning
confidence: 99%